PENINGKATAN HASIL BELAJAR SISWA MELALUI METODE ROLE PLAYING DENGAN PENDEKATAN CULTURALLY RESPONSIVE TEACHING (CRT) PADA MATA PELAJARAN PENDIDIKAN PANCASILA KELAS 6 SD 060852 MEDAN AREA - Juliana; Yaparno Famahato Daeli; Ade Putra Pulungan; Agung Jiwana; Helpi Suryani Manurung; Lia Muniar Lumbantoruan; Sarah Nur Suhaila Siregar (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
The learning of Pancasila Education in Class 6 of SDN 060825 Medan Area is the focus of this study. The Role-Playing method is used to improve students' understanding of the rights, obligations and responsibilities related to the environment and culture owned by students. Based on this study, students are less interested in Pancasila Education material because it is conventional and less interactive, which results in students not being involved and getting poor learning outcomes. On the other hand, through the Culturally Responsive Teaching (CRT) approach, the Role-Playing method makes learning more interactive and enjoyable, and student learning outcomes increase. Therefore, its implementation requires improved classroom management and teacher creativity. Therefore, this study suggests that teachers should be trained in implementing the Role-Playing method properly accompanied by scenarios that are adjusted to the student's environmental situation. They must also create interesting learning materials, use technology, and create a supportive learning environment. To find out how effective role-playing is, periodic evaluations are also needed. By implementing this recommendation, it is hoped that the quality of PKN learning in Class 6 of SDN 060825 Medan Area will increase significantly.